2016
DOI: 10.1515/popets-2016-0046
|View full text |Cite
|
Sign up to set email alerts
|

The Right to be Forgotten in the Media: A Data-Driven Study

Abstract: Due to the recent “Right to be Forgotten” (RTBF) ruling, for queries about an individual, Google and other search engines now delist links to web pages that contain “inadequate, irrelevant or no longer relevant, or excessive” information about that individual. In this paper we take a data-driven approach to study the RTBF in the traditional media outlets, its consequences, and its susceptibility to inference attacks. First, we do a content analysis on 283 known delisted UK media pages, using both manual invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…This has lead to the development of a set of proposed best practices from Data Protection Authorities for handling delisting requests [4]. In parallel, researchers have examined de-anonymization risks surrounding the RTBF [29].…”
Section: Originmentioning
confidence: 99%
“…This has lead to the development of a set of proposed best practices from Data Protection Authorities for handling delisting requests [4]. In parallel, researchers have examined de-anonymization risks surrounding the RTBF [29].…”
Section: Originmentioning
confidence: 99%
“…They wish to enable users to remove historical data about themselves from multiple systems, including removing results from leading search engines. Nevertheless, as we already suggest, those deleted content attract unwanted attention [42].…”
Section: Context and Motivationmentioning
confidence: 78%
“…Recent studies [16], [33] have shown that users extensively use this mechanism to protect the privacy of their past content-users delete around 35% of posts within six years of posting them. The European Union (EU) regulation of "Right to be forgotten" [41], [42] which is part of EU General Data Protection Regulation (GDPR) [4] is also trying to accomplish exactly this same, albeit at a much more elaborate scale. They wish to enable users to remove historical data about themselves from multiple systems, including removing results from leading search engines.…”
Section: Context and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers have different levels of privacy concerns for different types of information [48,49]. Consequently, it is not surprising that there is some evidence that European consumers' requests to apply the EU's recently established RTBF to have Google delist search engine results focus on some types of information more than others [50]. However, there are many other relevant forms of information that consumers may want deleted besides that which Google indexes (e.g., private social media posts restricted to friends, Internet of things data, mobile device sensory data, etc.).…”
Section: Discussionmentioning
confidence: 99%